ANALISIS KEPUASAN MAHASISWA PADA SEKOLAH TINGGI ILMU KESEHATAN PAYUNG NEGERI PEKANBARU - Engraini, Prahmadya; Sri, Restuti; Henni, Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to identify the level of student satisfaction on STIKES Payung Negeri Pekanbaru. The population is the student STIKES Payung Negeri Pekanbaru. Primary data was collected by questionnaire as an instrument to prove the result of research, to analyze the data used the importance performance analysis (IPA) method with the help of SPSS. The number of samples used as the object of research was 135 student using the purposive sampling method. The results of the study show that the student expectations bigger than reality obtained directly, This is caused by the ability of the campus that does not meet all student requests. However his hopes have not been fulfilled students feel satisfied with services that have been provided by STIKES Payung Negeri Pekanbaru.Keywords: Satisfaction, Students, STIKES Payung Negeri Pekanbaru